Pengaruh Kategori Pengobatan terhadap Keberhasilan Pengobatan Pasien Tuberkulosis - Nur Annisa; Sutanto Priyo Hastono (Jurnal Kesehatan Manarang, 2019)
Untreated tuberculosis disease will cause death after diagnosis in five years. The indicator of the success tuberculosis program can be measured by the success rate of treatment, the national standard of the success rate of treatment in Indonesia is 85%. The purpose of this study was determining the relationship of treatment category with the successful treatment at Poli Paru Rumah Sakit Umum Daerah Kota Cilegon Tahun 2017 with the confounding variables were age, gender, first sputum, comorbid diabetes mellitus and complications tuberculosis. A retrospective cohort study design was used in this study. We use data on tuberculosis patients who were registered in Sistem Informasi Tuberkulosis Terpadu (SITT) which began treatment in January to December 2017 until the treatment process was completed. Sampling was conducted by simple random sampling with hypothesis test for two-proportions of 113 people. We used multiple logistic regression test with causal models for data analysis. The results showed successfully treatment were 53 (46.9%) patients and a statistically significant relationship between the treatment categories and the successful treatment of TB (p value = 0.039) after being controlled by age, smear-positif before treatment, and other disease complications. Tuberculosis patients with category I treatment had odds 4.2 times higher to succeed than patients with category II treatment (OR = 4.2; 95% CI 1.077-16.41). The conclution of this study is treatment category among tuberculosis patients was determinant of success treatment. Increasing the success treatment can be sought by providing education in the community to immediately report and seek treatment if there are symptoms of tuberculosis.